2009
DOI: 10.1021/ol9013393
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Bromine−Magnesium Exchange Reactions in Heteroaryl Bromides

Abstract: Competition experiments are reported which compare the relative reactivities of bromoheteroarenes toward i-PrMgCl x LiCl in THF at 0 degrees C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
36
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 31 publications
6
36
0
5
Order By: Relevance
“…[2] Adeprotomagnesiation of arenes or heteroarenes can also be accomplished by using soluble hindered magnesium amides. [7] Furthermore,synthetically useful reagents for halogen-metal exchange are lithium organomagnesiates (R 3 MgLi). [7] Furthermore,synthetically useful reagents for halogen-metal exchange are lithium organomagnesiates (R 3 MgLi).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Adeprotomagnesiation of arenes or heteroarenes can also be accomplished by using soluble hindered magnesium amides. [7] Furthermore,synthetically useful reagents for halogen-metal exchange are lithium organomagnesiates (R 3 MgLi). [7] Furthermore,synthetically useful reagents for halogen-metal exchange are lithium organomagnesiates (R 3 MgLi).…”
mentioning
confidence: 99%
“…[15] Theaddition of TMEDA to iPrMgCl·LiCl [7] or sBu 2 Mg·2 LiCl [7b] had no effect. Full conversion with this reagent required areaction time of 8h.Switching to toluene showed that both of these reagents were unreactive.H owever, the addition of the new reagent sBuMgOR·LiOR (1a)t o4a in toluene provided 5a (X = OR·LiOR) in 85 %y ield within 15 min reaction time (entry 3).…”
mentioning
confidence: 99%
“…[9c-9e] This reactivity difference has also been observed in the bromine/magnesium exchange reactions. [11] Therefore, we started the study of the cross-couplings of 3-pyridyl bromides with arylboronic acids using 0.5 mol-% Pd(OAc) 2 in ethylene glycol at 80°C under air. The results are collected in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, the reaction with an unknown substrate should be monitored to estimate its rate, most conveniently by the GC analysis of the reaction mixture aliquots. Kinetics of the Br-Mg exchange reaction of several bromoheterocycles with isopropylmagnesium chloride-lithium chloride has been investigated in THF at 0 • C. 17 Interestingly, most heterocycles undergo the Br-Mg exchange significantly faster than bromobenzene. 2-Bromothiazole reacts about 10 7 times and 2-bromothiophene 1.5 × 10 5 times faster than bromobenzene, while 3-and 4-bromopyridines and 2-bromofuran react about 10 3 times faster.…”
Section: Halogen-magnesium Exchange Reaction Of Heteroarylmentioning
confidence: 99%